Can Multiple Attributes of Vegan Restaurants Affect the Behavioral Intentions by Customer Psychological Factors? - Park, Junghyun; Park, Yunmi; Yu, Jongsik (Frontiers in Nutrition, 2022)
Over the past decade, there has been an increased interest in veganism in several nations across the world. In 2021, there were around 79 million vegans. While veganism is growing, it still covers only 1% of the global population. But if the diet keeps its steady growth rate, it's predicted to increase to one in 10 people within the next 10 years. However, in addition to the traditional, though poorly studied, multiple attributes ascribed to vegan restaurants, there may be other factors influencing the approach intentions of vegan restaurant customers. Within this context, this study investigated the psychological resilience associated with customer engagement (identification, enthusiasm, attention, absorption, and interaction) with the vegan movement for Korean vegan customers. The analysis was conducted using SPSS 22.0 and AMOS 22.0. The results revealed that numerous attributes ascribed to vegan restaurants positively affected customer engagement, especially identification, and strongly influenced psychological resilience as well. However, the identification customer engagement factor did not significantly affect the approach intentions of vegan restaurant customers. The study results suggested that when eliciting customer engagement to increase approach intentions toward vegan restaurants, it is necessary to emphasize customer psychological resilience, enthusiasm, attention, absorption, and interaction. This study contributes to food and consumer behavior literature on the approach intentions toward vegan restaurants.